(untitled) (International Journal of Communication Systems and Network Technologies, 2022)
The multiband Microstrip Patch antenna is designed in CST simulation software for IoT (Internet of Things) application. In this paper, the antenna resonant frequency range was 100MHz and 5.8GHz, which is suitable for IoT application. The antenna is designed using CST simulation software operating in the frequency range of 5.8GHz. The antenna has a compact structure with dimensions of 60mm × 60mm × 1.6mm, modified as a ring hole. The proposed antenna can achieve a gain of 6.5dBi at a frequency of 5.8GHz and a maximum of 8.0dB. The power efficiency of the antenna is high, reaching 95.8%, and the voltage standing wave ratio(VSWR) is about 1.22. The bandwidth, size and stable electrical characteristics of this antenna make it successful for IoT applications.